Pelaksanaan Pembelajaran Pada Masa Pandemi Di SLB Negeri 1 Padang - Sari, Sri Multi; Taufan, Johandri (Jurnal Penelitian Pendidikan Khusus, 2021)
The purpose of this study is to know the implementation of learning and the constraints of learning implementation during the SMALB pandemic and how teachers deal with these obstacles, and evaluation. This study uses qualitative approach with case study type. The results describe the implementation of learning in SMALB during the pandemic which includes the implementation of learning, obstacles in the implementation of learning, the way teachers deal with obstacles, and evaluation. The curriculum used by classroom teachers is the 2013 curriculum. Teachers conduct learning in class while adhering to health protocols. The constraints felt by teachers during the implementation of classroom learning, less time and weak memory of children due to home visit learning in 2020. Teacher solutions in facing these obstacles so that learning objectives are achieved due to less than the maximum time teachers will adjust the learning indicators to the time. As for the memory of the child who is weak the teacher will repeat the learning until the child can. Evaluation on the implementation of teacher class learning using objective evaluation and essay after the end of learning.